A morte e o reino: reminiscências medievais no Romance d’A Pedra do Reino de Ariano Suassuna - Brito, Ewerton Matheus Menezes Sousa (2021)
The research propose to analyze how the representation of death, gender and the sacred court each other in the novel of A Pedra do Reino and the prince of the blood of the coming and goinf, written and published by the author Ariano Vilar Suassuna in full Civil-Military Dictatorship, analyzing certain uses of medieval reminiscences of the Iberian World in this work. In order to make this conecction between these two different worlds, we will use thinker Roberto Pontes theory of residuality, a theory that work on the hybrid conecctions that cultures and, consequently, literary works, maintain among themselves, in a constant recovery of elementes of othres societies that have survived, the residues. We developed the theory under the light of the History of Mentalities, particularly Phillippe Airès, in addition to clarifying the concepts of “tamed death”, “unnamed death”, residue, crystallization, Fields and haitus. Death, gender, good, evil, sex, sexuality, the beyond, past, presente and future are all linked, They are part of teleological whole, Only glimpsed by those brave enough to face the Moça Caetana and let herself bleed through her claws. Suassuana, a Christian man, backcountry and rural, creates a tragic and comic universe, crystallizing aspects of the medieval mentality about man facing death, time and the sacred in 20th century Brazil.